PENGARUH KUALITAS INFORMASI, PROMOSI, DAN KEMUDAHAN PENGGUNAAN TERHADAP KEPUTUSAN PEMBELIAN MELALUI KEPERCAYAAN PADA E-COMMERCE TRAVELOKA DI KABUPATEN JEMBER - br Gurusinga, Ispha Theresia; Irawan, Bambang; Endhiarto, Tatok (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of information quality and ease of use on purchasing decisions in Traveloka e-commerce through trust variable. This research was explanatory research. The population in this study were all consumers of Traveloka e-commerce in Jember Regency. This research technique applied non-probability sampling with a purposive sampling approach. The sample used in this study was 210 respondents who were at least 17 years and hadtransacted in Traveloka e-commerce. The method for collecting data in this study was the online survey using a questionnaire (Google Form). Path analysis was then applied as the analysis method in this study. The results show that information quality, ease of use and promotion have significant effect on trust. Moreover, the ease of use and trust have significant effect on purchashing decisions.